1966
DOI: 10.1111/j.1651-2227.1966.tb15258.x
|View full text |Cite
|
Sign up to set email alerts
|

Haptoglobin Level in Some Diseases of Infancy and Childhood

Abstract: Summary The level of serum haptoglobin was estimated in favism, thalassemia major, acute rheumatic fever, acute glomerulonephritis, nephrotic syndrome and virus hepatitis. In favism, it was totally absent during the haemolytic episode and then started to rise till it reached normal values after 6‐8 days. Ahaptoglobinaemia was persistent in patients with Thalassemia Major before and after treatment with blood transfusion, dexamethasone administration and splenectomy. In acute rheumatic fever, acute glomerulonep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

1967
1967
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…In any case, it seems that hemolysis, when present, is so moderate in thalassemia minor, that it cannot significantly affect the Hp turnover. The fall in Hp serum level in thalassemia major [1, 3, 5-7, 9, 10] and favism [1,2] is consistent with the hemolytic state and it could be predicted that Hp depletion in the latter should be more pronounced. There is indeed no doubt that the hyperacute hemolysis which occurs in favism represents a singular condition which during the course of 24-36 h affects about 75% or more of the total erythrocyte mass.…”
Section: Discussionmentioning
confidence: 92%
“…In any case, it seems that hemolysis, when present, is so moderate in thalassemia minor, that it cannot significantly affect the Hp turnover. The fall in Hp serum level in thalassemia major [1, 3, 5-7, 9, 10] and favism [1,2] is consistent with the hemolytic state and it could be predicted that Hp depletion in the latter should be more pronounced. There is indeed no doubt that the hyperacute hemolysis which occurs in favism represents a singular condition which during the course of 24-36 h affects about 75% or more of the total erythrocyte mass.…”
Section: Discussionmentioning
confidence: 92%
“…When the rate of Hp utilization exceeds that of production or release of this protein, the Hp concentration falls to levels too low to be measured. Because this glucoprotein was shown in one patient of Badr-El-Din et al [9] following infection, in 2 after milk injec tion and in our 9 cases, it is strongly suggested that ahaptoglobinemia in thalassemia is not due to the inability of the synthesis in general, but to increased consumption, as is usual in hemolytic anemia.…”
Section: Discussionmentioning
confidence: 98%
“…In one case Hp was determined only after splenectomy and in the rest only before splenectomy. The 2 patients of Badr-El-Din et al [9] were splenectomized without any rise in the Hp level due to this procedure, although it was stated that the Hb level was significantly raised in both. Since the hemolytic state per sists after splenectomy in thalassemia major, this finding is not at all surprising.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations